2020
DOI: 10.2478/pielxxiw-2020-0010
|View full text |Cite
|
Sign up to set email alerts
|

Coping with stress by Medical University students

Abstract: AbstractIntroduction. Stress can be defined as a physiological and psychic response to external stimuli (stressors) or as a relationship between the body and the environment that can affect the body in a negative, positive or neutral way.Aim. The aim of this paper was to investigate the causes of stress among students, and to identify methods of coping with it in relation to sociodemographic determinants. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
2
1
0
Order By: Relevance
“…frequently used problem-based strategies such as Active Coping and Planning and emotion-oriented ones, namely Seeking Emotional Support. Similar findings were reported bySzadowska-Szlachetka et al (2020) andBodys-Cupak et al (2018). These studies showed that the nursing students most frequently used strategies such as Active Coping, Seeking Emotional Support and Seeking Instrumental Support(Bodys-Cupak et al, 2018;Szadowska-Szlachetka et al, 2020).…”
supporting
confidence: 91%
See 1 more Smart Citation
“…frequently used problem-based strategies such as Active Coping and Planning and emotion-oriented ones, namely Seeking Emotional Support. Similar findings were reported bySzadowska-Szlachetka et al (2020) andBodys-Cupak et al (2018). These studies showed that the nursing students most frequently used strategies such as Active Coping, Seeking Emotional Support and Seeking Instrumental Support(Bodys-Cupak et al, 2018;Szadowska-Szlachetka et al, 2020).…”
supporting
confidence: 91%
“…Similar findings were reported bySzadowska-Szlachetka et al (2020) andBodys-Cupak et al (2018). These studies showed that the nursing students most frequently used strategies such as Active Coping, Seeking Emotional Support and Seeking Instrumental Support(Bodys-Cupak et al, 2018;Szadowska-Szlachetka et al, 2020). Most rarely did they use strategies directed at reducing bad emotions or resigning (Use of Psychoactive Substances, Cessation of Action).…”
supporting
confidence: 91%
“…Academic stress is defined as the interaction between environmental stressors, student's appraisal of them, and his/her reactions to them (Lee & Larson, 2000). Research indicates above-average stress levels among students (Waghachavare et al, 2013;Bore et al, 2016;Szadowska-Szlachetka et al, 2020) and higher levels of stress than in the general population (Bonneville-Roussy et al, 2017). Thus, university students are at higher risk among their peers in experiencing psychological distress (Larcombe et al, 2021).…”
Section: Academic Stressmentioning
confidence: 99%